Validation of Microepidendrum (Orchidaceae: Laeliinae) - Higgins, Wesley E. (Instituto de Ecología, A.C., 2002)
The generic name Microepidendrum Brieger ex W. E. Higgins is validated, an epitype of Epidendrum subulatifolium A. Rich. et Gal. is selected, and a new combination Microepidendrum subulatifolium (A. Rich. et Gal.) W. E. Higgins is proposed. Other species included in Microepidendrum by Brieger are excluded from the group. A phylogeny of the subtribe Laeliinae is presented showing the genus Microepidendrum Brieger ex W. E. Higgins to be sister to all other genera in Laeliinae and not closely related to Epidendrum or Encyclia.